THE GOVERNANCE OF ARTIFICIAL INTELLIGENCE: A COMPARATIVE POLICY ANALYSIS OF AI ETHICAL GUIDELINES IN SOUTHEAST ASIAN NATIONS - Dikdik Firman Sidik; Unggul Sagena; Mehriniso Davletova; Dildora Khodjaeva (Yayasan Adra Karima Hubbi, 2025)
The rapid development of Artificial Intelligence (AI) presents both opportunities and challenges for Southeast Asian nations, particularly in terms of governance and ethical considerations. While AI has the potential to drive economic growth and innovation, it also raises concerns about privacy, fairness, accountability, and transparency. However, the governance frameworks across Southeast Asia remain inconsistent, with countries at varying stages of implementing AI ethical guidelines. This study aims to conduct a comparative analysis of AI ethical policies across five Southeast Asian countries: Singapore, Malaysia, Indonesia, Thailand, and the Philippines. The research explores how these nations are addressing key ethical issues in AI governance and identifies gaps in their frameworks. A qualitative research design, using document analysis and semi-structured interviews with policymakers and experts, was employed to gather data on national AI strategies, regulations, and ethical guidelines. The findings reveal that Singapore and Malaysia have developed comprehensive and advanced AI ethics frameworks, while Indonesia and the Philippines are still in early stages of policy development. Thailand presents a balanced approach, focusing on both technological growth and social equity. The study concludes that there is a need for more coordinated AI governance in Southeast Asia to ensure responsible AI deployment that aligns with international ethical standards